FORMULASI MASKER GEL PEEL OFF EKSTRAK DAUN SIRSAK (Annona muricata L.) SEBAGAI ANTI JERAWAT - Junaedi; Yetri Elisya; Yusmaniar1; Tiara Insyirah Wijaya (Jurnal Farmasi IKIFA, 2023)
Acne is an inflammation of the skin due to increased production of sebum, keratinocytes, and the growth of Propionibacterium Acne bacteria so that pores are clogged. Soursop leaves (Annona Muricata L.) have a secondary metabolite that functions as an antibacterial, namely flavonoids. This study aims to determine the formulation of a peel-off gel mask from soursop leaf extract (Annona Muricata L.) which has the best characteristics. The physical evaluation includes organoleptic, pH, viscosity, dispersal power, adhesion, drying time, and stability test for 12 days of storage at temperatures of 4ºC and 40ºC. Research using experimental methods. Soursop leaf extract was extracted using percolation. The study was conducted using a peel-off gel mask preparation using concentration differences of 5%, 10%, and 15%. Based on the research that has been carried out, formula 4 is more preferred than other formulas because the results of the physical evaluation test of formula 4 meet all requirements. For the drying time test on formula 1 before and after the stability test, and formula 2 before the stability test the results did not meet the requirements, while for the dispersion test on formula 3 after the stability test, the results did not meet the requirements.